[Laiškas] / Rajecka (Raiecka) Sofija - Samueliui Rajeckiui. - (:unkn) unknown (My University, 1716)
1 laiškas apie vyro mirtį ir testamentu paliktą turtą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Rajecka (Raiecka), Sofija; Rajeckis, Samuelis